2019
DOI: 10.1108/nfs-02-2019-0053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the different times milk clotting in production artisanal Minas Frescal cheese

Abstract: Purpose The purpose of this study is to evaluate the yield, physico-chemical and microbiological parameters during the shelf life of the Minas Frescal cheese hand-manufactured by family farms. Design/methodology/approach In the milk, analyses of total bacterial counts, somatic cell counts and centesimal composition were performed. The milk coagulation was analyzed, with different curd times (40, 80 and 120 min), with respect to the proximate composition, pH, titratable acidity, yield and microbiological coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
0
1
Order By: Relevance
“…All protein values shown by Brazilian cheeses in the current study are higher than those observed by Resende et al (2020), who reported mean protein values of 15.9 ± 1.5% in samples of artisanal Minas frescal cheeses. Among the solid components of milk, proteins are important, both from a nutritional and technological point of view.…”
Section: Chemical Compositioncontrasting
confidence: 87%
See 1 more Smart Citation
“…All protein values shown by Brazilian cheeses in the current study are higher than those observed by Resende et al (2020), who reported mean protein values of 15.9 ± 1.5% in samples of artisanal Minas frescal cheeses. Among the solid components of milk, proteins are important, both from a nutritional and technological point of view.…”
Section: Chemical Compositioncontrasting
confidence: 87%
“…Although differences in the composition of Minas frescal cheeses were observed, similar results for moisture content (51.1 to 68%), ash (2.6 to 3.4%), lipids (21.0 to 34.9%) and proteins (13.5 to 18.6%) have already been reported in other studies (Cunha, Viotto & Viotto, 2006;Da Silva et al, 2017;Fritzen-Freire et al, 2010;De Jesus et al, 2020;Resende et al, 2020;Ribeiro, Simões & Jurkiewicz, 2009) 1.…”
Section: Chemical Compositionsupporting
confidence: 86%